Coupled analysis for the effect of wave height on FPSO motions - ., N Rini, VJ Kurian, MS Liew, A Whyte (2016)
Fully coupled time domain analysis is performed to study the effect of wave height on FPSO motions. The turret-moored FPSO used in the OTRC experimental studies were made use of to investigate the FPSO motion patterns. The study was conducted by varying the significant wave height for a particular peak period. The peak period ranges from 5–25 seconds, where the wave frequency response is significant.